Antiplatelet Therapy after Coronary Artery Bypass Grafting: Current Status and Future Perspectives - Comanici, Maria; Raja, Shahzad G. (British Journal of Healthcare and Medical Research, 2026)
Antiplatelet therapy is a critical component in managing patients undergoing coronary artery bypass grafting (CABG) to prevent graft occlusion and reduce thrombotic events. Current treatment options primarily include monotherapy with aspirin, dual antiplatelet therapy (DAPT), combining aspirin with a P2Y12 inhibitor, and, in some cases, triple therapy incorporating an anticoagulant. Recent advancements have focused on optimizing treatment regimens to balance the efficacy of antithrombotic protection with the associated risks of bleeding. Personalized treatment approaches, driven by patient-specific factors and genetic profiling, are increasingly recognized as essential for improving patient outcomes. Ongoing research aims to identify biomarkers that can predict patient responses to antiplatelet therapy, enabling more precise and effective treatment strategies. Additionally, novel therapeutic targets and new antiplatelet agents are being investigated to enhance the safety and efficacy of treatment. The results of these studies will shape the future of antiplatelet therapy and contribute to better clinical practices. The integration of genetic and pharmacogenomic data is anticipated to play a significant role in the personalization of antiplatelet therapy, ultimately leading to improved patient care in the context of CABG. This review article provides a comprehensive analysis of the current status and future perspectives of antiplatelet therapy in CABG.